PROFILE OF ACADEMIC BEGINNER TO COURSE FOR GRADUATE OF SCHOOL OF PHYSICAL EDUCATION ALAGOAS (Fiep Bulletin - online, 2013)
This study aimed to identify the profile of academic beginners to graduate students of Physical Education, Faculty of Alagoas from data collected with the application of the test of Cooper and cardiorespiratory fitness (VO2 max.). This search feature is the second Thomas & Nelson (2007) as descriptive of the kind of case study to study and provide information about the physical condition of academic beginners to graduate students of Physical Education, Faculty of Alagoas, and it also features ranks as the type of correlation studies by comparing the test results of Cooper with the VO2 max. From the collection of data in the Cooper test, the results were reasonable or regular and low values with 24.4% and 23% respectively; excellent 6.4% and 9% higher. Comparing the values found in the Cooper test and VO2 max, we find that reasonable or regular (42.3%) and low (25.6%) were those who also received the highest figures. Through the information provided here can see that the profile of academics is in, mostly, classified as regular or reasonable based on data of this study, then, supported the need for professionals in the health field, and especially the Educator Physical, in clarifying the role that physical activity plays in the life of man, as well as the advantages of its implementation with regard to cardiovascular problems, degenerative, hormonal, behavioral, psychological and emotional, interaction and social integration, among others.
Keywords: Profile; Quality of Life; Test Cooper